A meta-review of typologies of global citizenship education. Issue 2 (2nd April 2020) - Pashby, Karen; da Costa, Marta; Stein, Sharon; Andreotti, Vanessa
ABSTRACT: This paper reports on a reflexive exercise contributing a meta-mapping of typologies of GCE and supplementary analysis of that mapping. Applying a heuristic of three main discursive orientations reflected in much of the literature on GCE – neoliberal, liberal, and critical – and their interfaces, we created a social cartography of how nine journal articles categorise GCE. We found the greatest confluence within the neoliberal, greatest number within the liberal, and a conflation of different 'types' of GCE within the critical orientation. We identified interfaces between neoliberal-liberal and liberal-critical orientations as well as new interfaces: neoconservative-neoliberal-liberal, critical-liberal-neoliberal, and critical-post critical. Despite considerable diversity of GCE orientations, we argue GCE typologies remain largely framed by a limited range of possibilities, particularly when considered as implicated in the modern-colonial imaginary. In a gesture toward expanding future possibilities for GCE, we propose a new set of distinctions between methodological, epistemological, and ontological levels.